Iranian Brain Imaging Database: A Neuropsychiatric Database of Healthy Brain - Seyed Amir Hossein Batouli; Minoo Sisakhti; Shirin Haghshenas; Hamed Dehghani; Perminder Sachdev; Hamed Ekhtiari; Nicole Kochan; Wei Wen; Alexander Leemans; Mohsen Kohanpour; Mohammad Ali Oghabian (Basic and Clinical Neuroscience, 2021)
Introduction: The Iranian Brain Imaging Database (IBID) was initiated in 2017, with 5 major goals: provide researchers easy access to a neuroimaging database, provide normative quantitative measures of the brain for clinical research purposes, study the aging profile of the brain, examine the association of brain structure and function, and join the ENIGMA consortium. Many prestigious databases with similar goals are available. However, they were not done on an Iranian population, and the battery of their tests (e.g. cognitive tests) is selected based on their specific questions and needs. Methods: The IBID will include 300 participants (50% female) in the age range of 20 to 70 years old, with an equal number of participants (#60) in each age decade. It comprises a battery of cognitive, lifestyle, medical, and mental health tests, in addition to several Magnetic Resonance Imaging (MRI) protocols. Each participant completes the assessments on two referral days. Results: The study currently has a cross-sectional design, but longitudinal assessments are considered for the future phases of the study. Here, details of the methodology and the initial results of assessing the first 152 participants of the study are provided. Conclusion: IBID is established to enable research into human brain function, to aid clinicians in disease diagnosis research, and also to unite the Iranian researchers with interests in the brain.